Leadership styles of women principals in successful schools - Mustafa, Ismail (2004)
The role of women as principals has not been given much attention in the past. Women were not given sufficient chance to become administrators and leader of a school. It has always been a male-dominated field. The emergences of many schools with high academic achievement lead by women have changed the scenario, though. Women principals have proven they can lead as well if not better than their male counterparts. The purpose of this study is to examine the leadership styles of women principals in 13 successful schools in the state of Kedah which have shown mark improvement in the academic achievement based on the SPM examination result and the 5 stars awarded by Kedah State Education Department. The research sought to answer one major question. Are there any similarities in the leadership styles of these principals? Data was collected through cross sectional survey by using the Multi-factor Leadership Questionaire (MLQ) by Bass and Avolio (1988), consisting 4 dimensions of Transformational Leadership styles i.e. idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. The result of this research revealed that the 4 dimensions of Transformational Leadership are being practiced by the women principals. Three common behaviors were also identified; nurturing, collaboration and an orientation towards making changes for the benefit of students’ success. The study provides a better understanding of the leadership styles of women principals and perhaps this can be used as a benchmark for others.